Analisis Pelaksanaan Program Pos Pelayanan Terpadu (Posyandu) Remaja di Wilayah Kerja Puskesmas Jenggot Kota Pekalongan - Swasti Artanti; Ana Setyowati (Jurnal Kebidanan Harapan Ibu Pekalongan, 2024)
Sexual behavior in adolescents is increasingly closely related to modern lifestyles and tends to violate rules. For example, they will spend their free time doing negative things such as smoking, coming home late at night, taking drugs and accessing pornography. The phenomenon and desire for free sex in adolescents occurs in the form of pornographic films by 97%, kissing, fondling and oral sex by 93.7%, junior high and high school adolescents are no longer virgins 62.7%, junior high and high school adolescents 21.2% do abortion. The purpose of this study was to analyze the relationship between the level of hedonistic lifestyle and sexual behavior in class XI adolescents at SMK Bakti Purwokerto. Correlative quantitative analytic research method with a cross sectional design approach. The sample technique used was total sampling technique with 127 class XI students as respondents. The analysis of this study used univariate analysis in the form of a frequency distribution and bivariate analysis using the Spearman rho test. The results of this study are that there is a relationship between the level of hedonistic lifestyle and sexual behavior in class XI adolescents at SMK Bakti Purwokerto.